Monitoring skeletal muscle oxygen saturation kinetics during graded exercise testing in NCAA division I female rowers - Eserhaut, D. A.; DeLeo, J. M.; Provost, J. A.; Ackerman, K. E.; Fry, A. C. (Frontiers in Physiology, 2025)
Purpose: The purpose of this study was to analyze changes in skeletal muscle oxygen saturation (SmO2) kinetics during exercise in female rowers both acutely and longitudinally in relation to blood lactate (BLa). We also aimed to determine the agreement and statistical equivalence between physiological thresholds derived from SmO2 and BLa kinetics.